Analisa Pengaruh Kemiringan Sudut Screw Extruder Terhadap Keakuratan Diameter Filament 3D Printer Berbahan Recycled ABS, Recycled HDPE dan Polypropylene - Eka Nugroho, Fendra; Putri, Fenoria; Gunawan, Indra (MACHINERY Jurnal Teknologi Terapan, 2023)
New extruder with recydled HDPE material (oil bottle), ABS, Polypropylene. High quality filaments are characterized by high durability and constant diameter. In this study, we used material variables dan helix angles. Accumulation of plastic waste is a major problemÂ  in many countries, including Indonesia. On the other hand, there is also a rapidly growing technology, namely 3D printing. With the development of plastic based 3D Printing, it has become very important to make 3D printing innovations more environmentally friendly. This can be achieved by using 3D printing filaments made from recycled plastic. This research is envolving. Combining 0o , 15o, and 25o extrusion screwing with HDPE, ABS, and polypropylene materials, the average diameter isÂ  close to 1.75mm to 1.76mm. Because = 0.519553 > 0.05 (2;4) = 6,9443. However after receiving the optimization parameters, the final result shows a defect in filament quality. Make the surface rough and easy to bend. Therefore, it is not possible to create object on a 3D printer using filaments made of polypropylene and recycled ABS and HDPE plastic.